Effects of Saikosaponin D on CYP1A2 and CYP2D6 in HepaRG Cells - Li H; Tang Y; Wang Y; Wei W; Yin C; Tang F (Dove Medical Press, 2020)
Hongfang Li,1– 3,* Yunyan Tang,1,4,* Yang Wang,1– 3 Weipeng Wei,1– 3 Chengchen Yin,1– 3 Fushang Tang1– 3 1Department of Clinical Pharmacy, Key Laboratory of Basic Pharmacology of Guizhou Province and School of Pharmacy, Zunyi Medical University, Zunyi 563000, People’s Republic of China; 2Key Laboratory of Basic Pharmacology of Ministry of Education and Joint International Research Laboratory of Ethnomedicine of Ministry of Education, Zunyi Medical University, Zunyi 563000, People’s Republic of China; 3Key Laboratory of Clinical Pharmacy of Zunyi City, Zunyi Medical University, Zunyi 563000, People’s Republic of China; 4Department of Pharmacy, Meitan People’s Hospital, Zunyi 564100, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fushang TangDepartment of Clinical Pharmacy, Key Laboratory of Basic Pharmacology of Guizhou Province and School of Pharmacy, Zunyi 563000, People’s Republic of ChinaTel +86 851 2864 2337Fax +86 851 2864 2334Email fstang@vip.163.comBackground: Bupleurum is one of the most important traditional Chinese medicines and an ingredient in many compound preparations. It is widely used together with other drugs in clinical practice, and thus there is great potential for drug–drug interactions. Saikosaponin D (SsD) is a major bioactive triterpenoid saponin extracted from Bupleurum with anti-inflammatory, anticancer, antioxidative, and antihepatic fibrosis effects. Effects of the main components of Bupleurum on cytochromes P450 (CYPs) need to be clarified in the clinical application of combination therapies of formulations containing SsD or Bupleurum.Purpose: This study aimed to investigate the effects of SsD on the CYP1A2 and CYP2D6 mRNAs, protein expression, and relative enzyme activities in HepaRG cells.Methods: HepaRG cells were cultured with SsD at concentrations of 0.5, 1, 5 and 10 μM for 72 hours. mRNA and protein expression of CYP1A2 and CYP2D6 were analyzed with real-time PCR and Western blot analysis. Relative enzyme activities were analyzed with HPLC based on consumption of the specific probe substrate.Results: SsD significantly induced expression of mRNA and increased relative activity of CYP1A2 in HepaRG cells after the cells had been treated with SsD at concentrations of 1, 5 and 10 μM. SsD also induced protein expression of CYP1A2 at concentrations of 5 and 10 μM. SsD exhibited an inductive effect on CYP2D6 mRNA and protein expression, while increasing the relative activity of CYP2D6 at concentrations of 5 and 10 μM.Conclusion: This study is the first to investigate the effect of SsD on CYP1A2 and CYP2D6 in HepaRG cells, and the results may provide some useful information on potential drug–drug interactions related to clinical preparations containing SsD or Bupleurum.Keywords: saikosaponin D, HepaRG cells, drug–drug interactions